Impact of Prolonged COVID-19 Lockdown on Body Mass Index, Eating Habits, and Physical Activity of University Students in Bangladesh: A Web-Based Cross-Sectional Study - Hossain, Md. Jamal; Ahmmed, Foyez; Khan, Md. Robin; Rashid, Parisa Tamannur; Hossain, Sorif; Rafi, Md. Oliullah; Islam, Md. Rabiul; Mitra, Saikat; Emran, Talha Bin; Islam, Fahadul; Alam, Morshed; Sarker, Md. Moklesur Rahman; et al. (Frontiers in Nutrition, 2022)
Objectives This current study aims to assess the prevalence and factors associated with body mass index (BMI), dietary patterns, and the extent of physical activities among university students following the prolonged coronavirus disease 2019 (COVID-19) lockdown in Bangladesh. Methods A cross-sectional web-based survey was conducted between July 10 to August 10, 2021, through a pre-designed Google Form to collect the data from Bangladeshi university students (age: ≥18 years). Informed consent was electronically obtained from each participant, and a simple snowball technique was employed during the sampling. Frequency and percentage distribution, paired t-test, chi-square [χ2] test, and multinomial and binary logistic regression analyses were consecutively applied to analyze the collected data. Results Among the total participants (n = 1,602), 45.1% were female and 55.6% were 22–25 years' age group students. The BMI (mean ± standard deviation, SD) during the COVID-19 lockdown was 23.52 ± 7.68 kg/m2, which was 22.77 ± 4.11 kg/m2 during the pre-lockdown period (mean difference = 0.753; p < 0.001). The multinomial logistic regression analysis found a significant impact of gender [male vs. female: adjusted relative risk ratio (RRR) = 1.448; 95% confidence interval (CI) = 1.022, 2.053; p = 0.037], age (years) (<22 vs. >25: RRR =0.389, 95% CI = 0.213,0.710; p = 0.002, and 22–25 vs. >25: RRR = 0.473, 95% CI = 0.290, 0.772; p = 0.003), monthly family income (BDT) (<25,000 vs. >50,000: RRR = 0.525, 95% CI = 0.334,0.826; p = 0.005), university type (public vs. private: RRR = 0.540, 95% CI = 0.369, 0.791; p = 0.002), eating larger meals/snacks (increased vs. unchanged: RRR = 2.401, 95% CI = 1.597, 3.610; p < 0.001 and decreased vs. unchanged: RRR = 1.893, 95% CI = 1.218, 2.942; p = 0.005), and verbally or physically abuse (yes vs. no: RRR = 1.438, 95% CI = 0.977, 2.116; p = 0.066) on obesity during COVID-19 pandemic. Besides, the female students and those who have constant eating habits, were more likely to be underweight. Additionally, the binary logistic regression analysis found that the students from private universities [others vs. private: adjusted odds ratio (AOR) = 0.461, 95% CI = 0.313, 0.680; p < 0.001], urban areas (urban vs. rural: AOR = 1.451, 95% CI = 1.165, 1.806; p = 0.001), wealthier families (<25,000 BDT vs. >50,000 BDT: AOR = 0.727, 95% CI = 0.540, 0.979; p = 0.036), and who were taking larger meals/snacks (increased vs. unchanged: AOR = 2.806, 95% CI = 2.190, 3.596; p < 0.001) and had conflicts/arguments with others (no vs. yes: AOR = 0.524, 95% CI = 0.418, 0.657; p < 0.001), were significantly more physically inactive. Finally, the level of education and smoking habits significantly influenced the eating habits of university students during the extended strict lockdown in Bangladesh. Conclusion The current findings would be helpful tools and evidence for local and international public health experts and policymakers to reverse these worsening effects on students mediated by the prolonged lockdown. Several effective plans, programs, and combined attempts must be earnestly implemented to promote a smooth academic and daily life.